Management of obesity, insulin resistance and type 2 diabetes in children: consensus and controversy - Amy Fleischman (Dove Medical Press, 2009)
Amy Fleischman, Erinn T RhodesDivision of Endocrinology, Children’s Hospital Boston, Boston, MA, United StatesAbstract: Childhood obesity has become a national and international epidemic. The prevalence and incidence of type 2 diabetes in youth have been increasing, and type 2 diabetes is one of the most challenging complications of obesity in childhood. Comprehensive lifestyle interventions that include attention to dietary change, increased physical activity and behavior change appear to be required for the successful treatment of pediatric obesity. In particular, aspects of behavioral interventions that have been identified as contributing to effectiveness have included intensity, parent/family participation, addressing healthy dietary change, promoting physical activity, and involving behavioral management principles such as goal setting. A multidisciplinary team approach is required for successful management of type 2 diabetes in youth as well. As with many therapies in pediatrics, clinical trials and support for treatments of obesity and type 2 diabetes in youth lag behind adult data. Pediatric recommendations may be extrapolated from adult data and are often based on consensus guidelines. Type 2 diabetes in children is most commonly managed with lifestyle modification and medications, metformin and/or insulin, the only medications currently approved for use in children. However, many opportunities exist for ongoing research to clarify optimal management for obesity and type 2 diabetes in youth.Keywords: children, obesity, type 2 diabetes, metformin, insulin, bariatric surgery